Changes in polyunsaturated fatty acids are linked to metabolic syndrome in climacteric syndrome patients - Hua Ye; Linju Zhou; Qing Liu; Wanghua Xiao (Gynecological Endocrinology)
Objective This study explored the association between ω-6 to ω-3 polyunsaturated fatty acids (PUFAs) and metabolic syndrome in women experiencing climacteric syndrome.Methods The study involved 186 female participants and utilized surveys, anthropometric measurements (waist circumference, height, BMI, waist-to-height ratio), blood pressure assessments, and blood samples for lipid profile, glucose, insulin, HbA1c analysis. Serum PUFAs levels were analyzed using gas chromatography-mass spectrometry.Results The study found significantly higher measurements of waist circumference, waist-to-height ratio, systolic and diastolic blood pressure in postmenopausal women with metabolic syndrome compared to the control group. In addition, the metabolic syndrome group showed significantly higher levels of fasting blood glucose, triglycerides, low-density lipoprotein cholesterol, HbA1c, insulin, triglyceride to high-density lipoprotein ratio, and total cholesterol to high-density lipoprotein ratio. Furthermore, the study also identified significant differences among premenopausal women, postmenopausal women with metabolic syndrome, and postmenopausal women without metabolic syndrome in terms of omega-3 alpha-linolenic acid, omega-3 docosahexaenoic acid, omega-6 arachidonic acid, and omega-6 to omega-3 ratio.Conclusions We observed that high ω-6 arachidonic acid and ω-6/ω-3 ratio and low ω-3 ALA and ω-3 DHA were associated with high TG and WHtR. High TG and WHtR levels in postmenopausal women are associated with increased risk of Mets.